Pelatihan Penulisan Karya Ilmiah bagi Guru Bahasa Indonesia di Sekolah Menengah di Kota Ambon - Rumalean, Iwan; Solissa, Everhard Markiano (Jurnal Pengabdian Arumbai, 2025)
This community service activity was motivated by the limited ability of Indonesian language teachers in secondary schools in Ambon City to produce publishable scientific works. The aim of this program is to strengthen teachers’ academic literacy through structured, contextual, and sustainable training and mentoring in scientific writing. The method employed was Participatory Action Training (PAT), engaging teachers actively in needs analysis, intensive workshops, and post-training mentoring. The results indicated a significant improvement in teachers’ academic writing skills, digital reference management, and the establishment of an interschool teacher writing community. A total of 35 teachers completed their manuscripts, and 12 were recommended for publication in national journals. This activity successfully fostered a culture of academic writing and collaboration between schools and universities in island regions. The implication highlights that sustained mentoring and contextual approaches are effective strategies to enhance teacher professionalism and build a sustainable academic literacy ecosystem in areas with limited access to educational resources.